2003
DOI: 10.1021/ja028680o
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Polarity Control of Electron-Transfer Photochirogenesis. Enantiodifferentiating Polar Addition of 1,1-Diphenyl-1-alkenes Photosensitized by Saccharide Naphthalenecarboxylates

Abstract: Enantiodifferentiating polar photoaddition of alcohol to 1,1-diphenylpropene and 1,1-diphenyl-1-butene sensitized by saccharide naphthalene(di)carboxylates was performed in nonpolar to polar solvents containing methanol, ethanol, or 2-propanol as the nucleophile to give the corresponding anti-Markovnikov alcohol adduct, that is, 1,1-diphenyl-2-alkoxy-propane and -butane in low-to-good chemical yields, depending on the sensitizer, chiral auxiliary, alcohol, solvent, and temperature employed. The excited state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 53 publications
3
60
2
2
Order By: Relevance
“…In these photoreactions, radical anions generated from the electron-deficient molecules and carbon radicals generated from radical cations of the organosilicon compounds are postulated as reactive intermediates. However, control of stereoselectivity in the PET reaction has been less discussed so far [12][13][14][15]. We have previously reported that PET reaction of cycloalkylidenepropanedinitriles with allylic silanes afforded allylated products at a-carbon of cyano groups and reduction products in a highly diastereoselective manner [16].…”
Section: Introductionmentioning
confidence: 98%
“…In these photoreactions, radical anions generated from the electron-deficient molecules and carbon radicals generated from radical cations of the organosilicon compounds are postulated as reactive intermediates. However, control of stereoselectivity in the PET reaction has been less discussed so far [12][13][14][15]. We have previously reported that PET reaction of cycloalkylidenepropanedinitriles with allylic silanes afforded allylated products at a-carbon of cyano groups and reduction products in a highly diastereoselective manner [16].…”
Section: Introductionmentioning
confidence: 98%
“…24 -36 It was found that BSA has four hydrophobic pockets that bind one, three, two, and three AC molecules, respectively, in the order of decreasing affi nity. 25,37 Interestingly, AC bound to the fi rst binding site exhibits sharp fl uorescence similar to that in pentane and gives dual lifetimes of 4.8 and 2.1 ns, probably refl ecting the positional or orientational difference in the fi rst site. ACs bound to the second binding site of BSA have a lifetime of 13.2 ns, while those at third and fourth sites show broader fl uorescence with an identical lifetime of 15.8 ns, which is indistinguishable from that of AC in bulk water.…”
Section: Supramolecular Photochirogenesis With Biomoleculesmentioning
confidence: 99%
“…At an [AC]/[BSA] ratio of 3.6, 5b is given in 38% ee in the presence of 18 mM nitromethane added as a site -selective quencher, while 5c is produced in 58% ee in the absence of nitromethane. 25,37 HSA was also employed for mediating the photocyclodimerization of AC. It is known that HSA differs from BSA in only 26 amino acid residues out of ca.…”
Section: Supramolecular Photochirogenesis With Biomoleculesmentioning
confidence: 99%
“…Furthermore, if the photosensitizer is chiral, the polar addition would occur in an enantiodifferentiating manner to some degree. Thus, the photoaddition of 2-propanol to 1,1-diphenylpropene, when sensitized by chiral naphthalene(di)carboxylates, formed the anti-Markovnikov photoadduct with enantiomeric excesses of up to 58% [53]. Unfortunately, the reaction is far from attracting synthetic interest as the yields are still too low.…”
Section: Hào Additionmentioning
confidence: 99%